2001
DOI: 10.1021/ja0026509
|View full text |Cite
|
Sign up to set email alerts
|

Computing Handedness:  Quantized and Superposed Switch and Dynamic Memory of Helical Polysilylene

Abstract: Two new conjugating helical polymers comprising a rodlike silicon backbone and enantiopure chiral pendants, poly[(R)-3,7-dimethyloctyl-(S)-3-methylpentylsilylene] (PS-1) and its diastereomeric poly[(S)-3,7-dimethyloctyl-(S)-3-methylpentylsilylene] (PS-2), were prepared. Molecular mechanics calculations of PS-1 and PS-2 model oligomers indicated a double well potential energy curve corresponding to almost enantiomeric helices with dihedral angles of 150-160 degrees (P-motif, global minimum) and 200-210 degrees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 50 publications
4
45
0
Order By: Relevance
“…In the last two decades, we have designed and synthesized a wide range of polysilanes comprising chiral and/or achiral side groups. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] MF realized that polysilanes were gifted with unique features of exhibiting intense and sharp UV absorption, circular dichroism (CD), and photoluminescence (PL) spectra around 300-400 nm, characteristic of the r-conjugation in the helical silicon-catenated main chain. Individual rod-like helical polysilanes in solution afford a highly intense, narrow exciton absorption band along with a sharp mirror-imaged emission band.…”
Section: Helical Polysilanesmentioning
confidence: 99%
“…In the last two decades, we have designed and synthesized a wide range of polysilanes comprising chiral and/or achiral side groups. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] MF realized that polysilanes were gifted with unique features of exhibiting intense and sharp UV absorption, circular dichroism (CD), and photoluminescence (PL) spectra around 300-400 nm, characteristic of the r-conjugation in the helical silicon-catenated main chain. Individual rod-like helical polysilanes in solution afford a highly intense, narrow exciton absorption band along with a sharp mirror-imaged emission band.…”
Section: Helical Polysilanesmentioning
confidence: 99%
“…The acidbase reaction of the corresponding cobalt complex triggered the interconversion of coordinating atoms between amide nitrogen atoms and amide oxygen atoms, giving rise to a stretching (extension/contraction) molecular motion. Since we previously demonstrated that the helicity of the Co II complex with H 2 L2 was dynamically inverted from the L cis-a form to the D cis-a form by adding achiral NO 3 À ions, [4][5][6] the employed H 2 L1-Co II complex was designed to work as a novel type of molecular machine that exhibits coupled stretching and inverting motions. Several types of helical ligands have shown extension/contraction molecular motion on metal complexation/decomplexation [2d-e, 7] and/or protonation/deprotonation, [7, 8] but the present type of kinetically labile Co II complex allows a dual molecular motion in a highly dynamic fashion, as would be required for a sophisticated supramolecular switching device.…”
mentioning
confidence: 99%
“…Switching of the macromolecular helicity of dynamic helical polymers controlled by chiral stimuli is quite interesting, but is still a challenge 20–25 (For inversion of the macromolecular helicity observed in other helical polyisocyanates and polysilanes, see Ref. 22–25). We found that the poly‐1 enantioselectively underwent the inversion of helicity in an aqueous solution in the presence of a hydrophobic guest, 1,1′‐2‐binaphthol ( 3 ).…”
Section: Resultsmentioning
confidence: 99%